2011
DOI: 10.3390/ijms12096176
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Some New Azo Photoisomerizable Bismaleimide Derivatives

Abstract: Novel polythioetherimides bearing azobenzene moieties were synthesized from azobismaleimides and bis-2-mercaptoethylether. Kinetics of trans-cis photoisomerization and of thermal conversion of cis to trans isomeric forms were investigated in both polymer solution and poly(methyl methacrylate) doped films using electronic absorption spectroscopy. Thermal recovery kinetics is well described by a two-exponential relation both in solution and polymer matrix, while that of low molecular weight azobismaleimide fit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…For ABM 2 in DMF solution, they obtained the photoisomerization rate constant of (3.31 ± 0.03) × 10 −2 •s −1 . Whereas, the rate constant of photoisomerization process for ABM 1 was about two times lower than that of ABM 2 [29]. These values are similar to our results; however, it should be noted that in the case of studied quinoline azo-dye polymers the photoisomerization rate constant was measured for materials in the form of thin films.…”
Section: Uv-vis Measurementssupporting
confidence: 89%
“…For ABM 2 in DMF solution, they obtained the photoisomerization rate constant of (3.31 ± 0.03) × 10 −2 •s −1 . Whereas, the rate constant of photoisomerization process for ABM 1 was about two times lower than that of ABM 2 [29]. These values are similar to our results; however, it should be noted that in the case of studied quinoline azo-dye polymers the photoisomerization rate constant was measured for materials in the form of thin films.…”
Section: Uv-vis Measurementssupporting
confidence: 89%
“…Morley and co-workers (Morley et al 2004 ) suggested that a greater localization of spin density at the reactive azo nitrogen atoms in the excited triplet state may be correlated with the lower photochemical stability of some azobenzene derivatives. The experimental results showed that azo derivatives 2 and 3 provide high yields of the (Z) isomers at irradiation with UV light (365 nm) (Airinei et al 2011b ).
Figure 12 Structure and spin density distribution (shown as green spheres) of the first excited triplet state (T 1 ) for a) (E)-1 and b) (E)-3 computed by AM1 method.
…”
Section: Resultsmentioning
confidence: 99%
“…The titles of these compounds are listed as follows, (E)-1: (E)-1-(4-(phenyldiazenyl)phenyl)-1H-pyrrole-2,5-dione; (Z)-1: (Z)-1-(4-(phenyldiazenyl)phenyl)-1H-pyrrole-2,5-dione; (E)-2: (E)-4-(2,5-dioxo-2 H -pyrrol-1(5 H )-yl)- N -(4-(phenyldiazenyl)phenyl) benzamide; (Z)-2: (Z)-4-(2,5-dioxo-2 H -pyrrol-1(5 H )-yl)- N -(4-(phenyldiazenyl)phenyl)benzamide; (E)-3: ( E )-1,1’-(4-( p -tolyldiazenyl)-1,3-phenylene)bis(1 H -pyrrole-2,5-dione); (Z)-3: ( Z )-1,1’-(4-( p -tolyldiazenyl)-1,3-phenylene)bis(1 H -pyrrole-2,5-dione); (E)-4: ( E )-1,1’-(4-( o -tolyldiazenyl)-1,3-phenylene)bis(1 H -pyrrole-2,5-dione); (Z)-4: ( Z )-1,1’-(4-( o -tolyldiazenyl)-1,3-phenylene)bis(1 H -pyrrole-2,5-dione). The synthesis and characterization details (experimental part) of these azobenzene derivatives containing maleimide moieties have been reported previously (Airinei et al 2010 ; Rusu et al 2011 ; Hulubei & Buiceac 2005 ; Airinei et al 2011a , 2011b ).
Figure 1 Chemical structure of azobenzene derivatives considered for molecular modeling.
…”
Section: Methodsmentioning
confidence: 93%
“…All the intermediates and the target molecules were purified by column chromatography, and the new compounds were characterized by 1 H NMR, 13 C NMR, FT-IR, and MALDI/TOF mass spectrometry. It was found that the vinyl groups in the synthesized compounds adopted the trans-conformation on account of the absence of the signal at 6.56 ppm in 1 H NMR spectra, which was assigned to the proton in the cis-form [18]. In addition, in the FT-IR spectra of 1 and 2 the appearance of the vibration absorption at ca.…”
Section: Synthesis and Characterizationsmentioning
confidence: 97%